Correction: Gender and Social Contacts: Labour Market Entry Among Refugee and Family Reunion Migrants in Sweden - Rosa Weber (Nordic Journal of Migration Research)
This article details a correction to: Weber, R. (2024) ‘Gender and Social Contacts: Labour Market Entry Among Refugee and Family Reunion Migrants in Sweden’, Nordic Journal of Migration Research, 14(3), 4. Available at: https://doi.org/10.33134/njmr.664.